In vitro virucidal activity of mouthwashes on SARS‐CoV‐2. (25th April 2022) - Buonavoglia, Alessio; Lanave, Gianvito; Marchi, Serena; Lorusso, Pantaleo; Montomoli, Emanuele; Martella, Vito; Camero, Michele; Prati, Carlo; Trombetta, Claudia Maria
Abstract: Objectives: The objective of the study was to evaluate the in vitro virucidal activity of commercial mouthwashes against SARS‐CoV‐2 and variants of concern. Materials and Methods: Antiviral activity was assessed at different time intervals, based on common use of these products by titrating residual viral infectivity on Vero E6 cells. Results: All the mouthwashes were effective to reduce the infectious titers of SARS‐CoV‐2 and its tested variants. Mouthwashes Listerine ® Cool Mint milder taste and Listerine ® Cavity Protection milder taste reduced the infectious viral titer by up to 3.9 log10 after 30 s, while mouthwash Cetilsan ® Sugar Free was able to reduce the viral titer by 2.2–2.9 log10 at all tested time intervals. Mouthwash Curasept ® ADS DNA Intensive treatment was less effective to decrease viral infectivity (0.7–2.2 log10 TCID50/ml at all tested time intervals). Interestingly, the Gamma variant appeared more resistant to treatment in vitro with the different mouthwashes. Conclusions: In this study, we were able to assess the ability of different mouthwashes to in vitro decrease the infectivity of SARS‐CoV‐2 and its variants, and we observed that Gamma variant of concern was more resistant to treatment with mouthwashes.